Corruption and Economic Growth at Province Levels in Indonesia - Nairobi, Nairobi (Universitas Negeri Semarang, 2021)
This study aims to determine the effect of corruption on economic growth at the provincial level in Indonesia. This study uses a model based on the economic growth model of Levine and Renelt (1992). This study uses secondary data obtained from the Central Statistics Agency (BPS), the Investment Coordinating Board (BKPM), and Transparency International Indonesia with the research period of 2014-2018. This study uses a panel data model with a cross-section of 16 (sixteen) provinces in Indonesia. This study uses a model with a Random Effect Model (REM) approach. The results showed that the corruption perception index, foreign direct investment (FDI), initial growth (EGt-1), government spending (GE) and labor (L) each had a positive and significant effect on economic growth (EG) in 16 provinces in Indonesia for the 2014-2018 period, ceteris paribus.